Oral Treatments With the TrkB Ligand Prodrug, R13, Promote Enhanced Axon Regeneration Following Peripheral Nerve Injury - English, Arthur W.; Carrasco, Dario; Hoffman, Dustin; Isaacson, Robin; Kang, Seong Su; Khan, Samia; Liu, Xia; Ye, Keqiang (Frontiers in Cellular Neuroscience, 2022)
Axon regeneration after peripheral nerve injury is slow and inefficient, leading to generally poor functional recovery. Activity-dependent experimental therapies that increase expression of brain-derived neurotrophic factor (BDNF) and its TrkB receptors enhance regeneration, suggesting that treatments with BDNF might also be effective. However, recombinant human BDNF (rhBDNF), as well as 7,8-dihydroxyflavone (7,8-DHF), a small molecular BDNF mimetic, may have limited treatment applications because of their modest oral bioavailability and pharmacokinetic profile. R13 is a 7,8-DHF prodrug. Upon oral administration, it is converted in the liver to 7,8-DHF. In immunoblots from tissues at the site of nerve injury, a single oral treatment with R13 to mice following sciatic nerve transection and repair produced a rapid and prolonged increase in immunoreactivity to phosphorylated TrkB, prolonged phosphorylation of mitogen activated protein kinase (MAPK/Erk1/2), and a rapid but transient increase in phosphorylated AKT (protein kinase B). Intramuscular injections of fluorescent retrograde tracers into the gastrocnemius and tibialis anterior muscles four weeks after nerve injury resulted in significantly greater numbers of labeled motoneurons and dorsal root ganglion neurons in R13-treated mice than in vehicle-treated controls. Direct electromyographic (EMG) responses (M waves) were significantly larger in R13-treated mice four weeks after injury than vehicle-treated controls or mice treated with oral 7,8-DHF. Oral treatments with the prodrug, R13, are a potent therapy for stimulating axon regeneration and functional recovery after peripheral nerve injury.